PENGARUH PEMBELAJARAN KONTEKSTUAL TERHADAP KETERAMPILAN MENULIS PUISI KELAS III SDN 66 PONTIANAK KOTA - Olivia, Karina; Halidjah, Siti; Suparjan, Suparjan (Universitas Tanjungpura, 2022)
AbstractThis study aims to see the presence and magnitude of the influence of contextual learning on poetry writing skills for class III SDN 66 Pontianak City. The research method used is an experimental method, in the form of Quasi Experimental Design, Non-Equivalent Control Group Design. In this study, the population was all third grade students consisting of 52 students. The sampling technique used nonprobability sampling technique, namely purposive sampling, so that the sample obtained was 26 students in class III A as the experimental class and 26 students in class III B as the control class. The data collection technique used is a measurement technique using a written test to complete/write a missing poem. The results of data analysis showed that the post-test average for the control class was 55.88 and the posttest average for the experimental class was 68.58. The results of the study were processed by t-test obtained t_count (3.676) and t_table (Î± = 5% and dk = 26 + 26